Efficacy of acupuncture for functional constipation in elderly: a systematic review and meta-analysis - Song, ShiWei; Hao, WenFeng; Fu, HongFang (Frontiers in Medicine, 2024)
Background: More clinical studies have shown that patients suffering from functional constipation can benefit from combining medicine and acupuncture. There have been no published reviews or meta-analyses of the use of acupuncture in treating functional constipation in older adults. As a consequence, we carried out a meta-analysis to assess the impact of acupuncture on elderly patients dealing with functional constipation.Methods: This study retrieved RCTs of acupuncture therapy for functional constipation in the elderly from several electronic databases, including Embase, PubMed, Cochrane Library, Wang-fang database, Chinese BioMedical Literature Database, and China National Knowledge Infrastructure. In these databases, clinical investigators evaluated the effectiveness of acupuncture as a primary treatment for old people with functional constipation. The Cochrane Handbook for Systematic Reviews of Interventions was used by clinical investigators to evaluate the quality of the study.Results: A total of 469 elderly individuals were included in 8 RCTs. The meta-analysis yielded compelling findings: the application of acupuncture has significantly elevated the rates of treatment effectiveness when juxtaposed with the control group. Compared with the control group, the treatment group had a statistically significant difference in complete spontaneous bowel movements after treatment. The two groups showed no significant difference in spontaneous bowel movements.Regarding the Bristol Stool Scale score, there is a significant difference. The defecation difficulty score and PAC-QOL had p-values indicating no significant effect. However, acupuncture increased changes in bowel movements; there was a significant difference in comparing the CCS between the two groups. The NOS and 5-HT contents were changed significantly after intervention in both groups.An article reported the improvement of Traditional Chinese Medicine symptom scores was better in the treatment group than in the control group.The analysis results indicated that acupuncture was beneficial in elderly people with functional constipation; however, strong, comprehensive data are not yet obtainable. Given that our study is underpinned by evidence of a low-to-moderate level, we need more high-quality research to enhance the feasibility and practicability of this treatment. Systematic review registration: PROSPERO, identifier no. CRD42024533215.